Elucidating the structural dynamics induced by active site mutations in 3C protease of foot-and-mouth disease virus - Sthitaprajna Sahoo; Hak-kyo Lee; Donghyun Shin (PLoS ONE, 2025)
The viral replication of foot-and-mouth disease virus (FMDV) and other picornaviruses primarily depends on the successful processing of a polyprotein precursor by the enzyme 3C protease (3Cpro) at specific sites. The crucial role of 3Cpro in viral replication and pathogenesis makes it a potential target for developing novel therapeutics against foot-and-mouth disease. The β-ribbon region (residues 138–150) containing the active site residues (C142) in 3Cpro is found to be conserved and contributes significantly to substrate specificity. Moreover, experimental reports suggest that mutations at position 142, particularly C142S and C142L, exhibit different functional activities. However, the intrinsic dynamics and conformational changes induced by active-site mutations of 3Cpro remain unclear, limiting the development of novel inhibitors of 3C protease. Accordingly, we carried out molecular dynamics (MD) simulations with multiple replicates for both the WT and mutants of 3Cpro. The observed results suggest that the C142S mutant induces substantial structural transitions compared to the WT and C142L. In contrast, the essential dynamics of the mutants significantly varied from those of the WT 3Cpro. Moreover, cross-correlation analysis revealed a similar pattern of anti-correlation between the amino acid residues of the WT and C142L mutant complexes. Analysis of the betweenness centrality of the WT and the mutants from the residue interaction networks revealed common residues for intra-residual signal propagation. The results from our study suggest that the active site mutant C142S may induce conformational changes, which can cause the β-ribbon region to bend towards the catalytic pocket and inhibit the enzymatic activity. C142L substitution may also alter the β-ribbon region conformation, which may impact the substrate binding process during proteolysis, as reported in previous studies. These results can provide a better understanding of the conformational dynamic behavior of 3Cpro active-site mutants and may assist in developing potential inhibitors against foot-and-mouth disease.